Analisis Kebutuhan Bahan Ajar Interaktif Berbantuan Canva pada Materi Menulis Teks Prosedur Bermuatan Kearifan Lokal Banyumas - Dimas Yusuf Afrizal; Hera Septriana; Ahmad Fauzan Iswahyudi; Muhammad Sidiq Pambudi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study aimed to analyze students’ needs for the development of Canva-assisted interactive teaching materials on writing procedure texts, integrated with the local wisdom of Banyumas Regency. The study employed a quantitative approach using a survey method. The participants consisted of 71 seventh-grade junior high school students. Data were collected through a needs-analysis questionnaire consisting of 10 statements, measured on a 4-point Likert scale. The data were analyzed using descriptive statistics, including frequency, percentage, and mean scores. The findings revealed that students had a strong need for Canva-assisted interactive teaching materials. The highest percentage was found in the learning preference indicator (85.04%), followed by the need for the integration of local wisdom (80.28%), the need for digital teaching materials (80.16%), contextual learning (79.93%), and learning experience and difficulties (74.30%). These findings indicate that students require visually engaging teaching materials that are easily accessible through digital devices and integrate the local wisdom of Banyumas Regency into the teaching of procedure text writing. The results of this needs analysis provide an empirical basis for developing Canva-assisted interactive teaching materials that are aligned with students’ learning characteristics and needs